COST ANALYSIS OF A COST-PLUS CONTRACT. - Kelley, Arthur C. (The Accounting Review, 1942)
Abstract The great problem in the administration of the cost-plus contract program is the prevention of inflated and unnecessary costs. The fact that the government guarantees to reimburse the contractor for all necessary costs of performing the contract and in addition to pay a fixed fee, has often resulted in a let-down on the part of the contractor of his guard against high costs. It is the purpose of this article to draw attention to the merits and disadvantages of the cost-plus contract and to consider what devices and means can be used to make this type of contract function more efficiently as a method of producing goods. The production of goods under a cost-plus contract bears a similarity to monopolistic production, since the free market is abolished and all costs are recovered from the government. If the cost-plus program, therefore, is to become a vital and successful part of the American economic system, ways and means must be found for injecting efficiency into this type of production.